The genetic basis of gram-negative bacteria resistant to antimicrobials isolated from invasive infections in the Republic of Moldova - ANTON, Maria (One Health & Risk Management, 2024)
Introduction. Despite the efforts made and measures taken to combat antimicrobial resistance, alarming levels of resistance in gram-negative bacteria continue to be reported on a global scale. The antimicrobial resistance mechanisms of these bacteria represent the main cause of therapeutic failures.Material and methods. A retrospective analysis of strains of E. coli, K. pneumoniae, P. aeruginosa, and A. baumannii isolated from patients with invasive infections was conducted for the period 2020-2023. Screening for carbapenemase-producing strains was performed based on sensitivity to antimicrobial agents tested using the Vitek-2 compact automated system. Confirmation of resistance mechanisms was achieved through multiplex PCR molecular biology technique. Results. The analysis of the obtained data indicates high resistance among strains of K. pneumoniae to fluoroquinolones (77.2%), while the majority of E. coli strains were resistant to penicillins (53.5%). Concerningly, non-fermentative bacilli strains also present alarming figures, with over 60.0% of P. aeruginosa strains resistant to penicillins, cephalosporins, fluoroquinolones, carbapenems, and over 80.0% of A. baumannii strains resistant to all tested antimicrobial groups. The resistance enzyme OXA-48 was detected in 91.7% of K. pneumoniae strains and 15.6% of E. coli strains, while the blaNDM resistance gene was detected in 15.9% of P. aeruginosa isolates, and the blaOXA-23 gene was identified in 55.2% of A. baumannii isolates.Conclusions. The rapid identification of multi-drug resistant gram-negative bacilli ensures the success of therapy for infections caused by them, and monitoring resistance profiles is an essential step for subsequent actions to combat antimicrobial resistance.